Workplace Spirituality and Innovative Work Behavior: Unveiling the Power of Engagement - Margaretha, Meily; Sudiro, Achmad; Kurniawati, Desi Tri; Prabandari, Sri Palupi (International Review of Management and Marketing, 2025)
This study aimed to examine the influence of workplace spirituality (WpS) on innovative work behavior (IwB) with employee engagement (EmE) as a mediating variable. By using a quantitative method, data were collected from 251 respondents from the public and private sectors in Indonesia with a minimum of 1 year of work experience. The analysis was conducted using Partial least squares structural equation modelling (PLS-SEM). The results showed that workplace spirituality had a significant positive effect on employee engagement and innovative work behavior, both directly and indirectly. Furthermore, employee engagement played a partial mediating role, suggesting that it served as an important psychological mechanism in translating spiritual values into innovative actions. The results reinforced existing literature and expanded the understanding of how spiritual values were internalized in the context of innovative work behavior. Values such as meaningful work, connectedness between colleagues, and inner harmony were found to foster a work climate that motivated exploration, the courage to take initiative, and bottom-up innovation. This study further recommended the integration of spirituality into organizational culture as a holistic strategy to increase engagement, enhance well-being, and drive sustainable innovation in the modern workplace.